2015
DOI: 10.2147/ppa.s78178
|View full text |Cite
|
Sign up to set email alerts
|

Development of the CoMac Adherence Descriptor™: a linguistically-based survey for segmenting patients on their worldviews

Abstract: Nonadherence to prescribed medication and healthy behaviors is a pressing health care issue. Much research has been conducted in this area under a variety of labels, such as compliance, disease management and, most recently, adherence. However, the complex factors related to predicting and, more importantly, understanding and explaining adherence, have nevertheless remained elusive. However, through an in-depth linguistic analysis of patient talk, the International Center for Intercultural Communication (ICIC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The research identified linguistic indicators in the way patients talk that include agency (high/takes charge, low/does not take charge), affect (positive/upbeat, negative/downbeat), and control orientation (internal/looks to self for directions, external/looks to others for directions). The linguistic features of these three well-studied psychosocial constructs related to type 2 diabetes mellitus self-management and adherence were subsequently applied to the development of a survey questionnaire, the CoMac Descriptor 9. The 12-question survey has a reading level at the sixth-grade level.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The research identified linguistic indicators in the way patients talk that include agency (high/takes charge, low/does not take charge), affect (positive/upbeat, negative/downbeat), and control orientation (internal/looks to self for directions, external/looks to others for directions). The linguistic features of these three well-studied psychosocial constructs related to type 2 diabetes mellitus self-management and adherence were subsequently applied to the development of a survey questionnaire, the CoMac Descriptor 9. The 12-question survey has a reading level at the sixth-grade level.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, we report a pilot implementation of an innovative language-centered communication tool, the CoMac Communication System. The CoMac System starts with the inherent assumption that language of the patient reveals his/her beliefs, worldviews, and orientation to self-management 5–9. Through understanding the person’s orientation through language, this approach provides the clinician with tools for individualized advice and person-centered communication.…”
Section: Introductionmentioning
confidence: 99%
“…The CoMac Descriptor™ for hypertension was originally developed using the language of US patients gathered in interviews. 25 The online instrument was linguistically based in two senses. First, it was created from lengthy interviews of patients, and second, the actual language of the patients who had been classified as belonging to different domains was used to craft response options in the questions.…”
Section: Objectives and Methodsmentioning
confidence: 99%